Emissions trading institutional design, decision making and corporate strategies - Antes, Ralf; Hansjürgens, Bernd; Letmathe, Peter; Pickl, Stefan (Springer eBooks., 2011)
Emissions trading challenges the management of companies in an entirely new manner: Not only does it, like other market-based environmental policy instruments, allow for a bigger flexibility in management decisions concerning emission issues. More importantly, it shifts the mode of governance of environmental policy from hierarchy to market. But how is this change reflected in management processes, decisions and organizational structures? The contributions in this book discuss the theoretical implications of different institutional designs of emissions trading schemes, review schemes that have been implemented in the US and Europe, and evaluate the range of investment decisions and corporate strategies which have resulted from the new policy framewo